The legacy of Black Consciousness: Its continued relevance for democratic South Africa and its significance for theological education - Dolamo, Ramathate Tseka Hosea (HTS teologiese studies, 2017)
This article argues that Black Consciousness as a philosophy transcends all political organisations and ideologies, because its architects were interested in rallying the whole country to fight apartheid regardless of political affiliation. The same consciousness that was raised in the 1960s could still influence political business today in democratic South Africa. To this end, a selection of values and principles of Black Consciousness has been examined that could be used in various sectors to ensure that our democracy is strengthened and protected. Some of those values and principles include: (1) a sense of solidarity in the face of adversity; before 1994, it was apartheid and today it is poverty; (2) the importance of the value of self-reliance in the face of unemployment and joblessness; (3) the value of self-understanding in Africa and globally as a country and (4) the critical role that education plays towards the total liberation of the whole person.